Pendampingan Penerapan Sistem Penetuan Minat dan Bakat di RA Kusuma Mulya Rohmah Kabupaten Kediri - Pamungkas, Danar Putra; Rochana, Siti; Helilintar, Risa; Ramadhani, Risky Aswi; Wahyuniar, Lilia Sinta (Jurnal Pengabdian Masyarakat Nusantara, 2024)
Determining interests and talents is very necessary to determine a child's potential both academically and non-academicly. This knowledge is very necessary in directing and developing skills that are appropriate to the child's abilities. RA Kusuma Mulia Rohmah does not yet have a clear and structured system for determining student interests and talents. Assistance is needed to implement the interest determination system. This Talent Interest Determination System can be used to analyze and determine the talents and interests of children aged 5-7 years, analyze Academic, Creative, Artistic, Kinestatic and Social Talent Systems and can be applied to the new student selection process